2021
DOI: 10.1109/access.2021.3133360
|View full text |Cite
|
Sign up to set email alerts
|

Novel Neural Network-Based Load Frequency Control Scheme: A Case Study of Restructured Power System

Abstract: Nowadays, neural networks (NN) are being utilized in different control problems because of their excellent ability to model any nonlinear process. NN is suitable for the process having a wide range of operating conditions. In this work, the neural network-based internal model control (NN-IMC) scheme has been considered as a secondary controller for the load frequency control (LFC) problem in the restructured electricity market in order to meet Poolco and bilateral transactions. The proposed control scheme has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Testing was performed on IEEE39 and NRPG 246 models. In works [101][102][103][104][105], the RL, PSO, BBBC, GA, and DQN algorithms were used to solve the FC problem. In this section, 11 articles devoted to methods for selecting CAs for FC EPS based on ML algorithms were considered.…”
Section: Providing Acceptable Frequency Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing was performed on IEEE39 and NRPG 246 models. In works [101][102][103][104][105], the RL, PSO, BBBC, GA, and DQN algorithms were used to solve the FC problem. In this section, 11 articles devoted to methods for selecting CAs for FC EPS based on ML algorithms were considered.…”
Section: Providing Acceptable Frequency Levelsmentioning
confidence: 99%
“…BBBC [103] 75-bus real power system --High performance, less overshoot, and fast damping of the regulation process.…”
Section: Pso [102] ---mentioning
confidence: 99%
“…To meet Poolco and bilateral transactions in the restructured electricity market, a neural network-based internal model control system (NN-IMC) was considered as a secondary controller for the load frequency control problem (LFC) [252]. The test system is divided into four areas to carry out the analyses.…”
Section: Artificial Neutral Network (Ann)mentioning
confidence: 99%
“…Therefore, it was found that the NN-IMC control scheme performed well and effectively improved the system's responses. After subsequently carrying out a comparative analysis of the performances of the NN-IMC control scheme with those of the fractional-order PID (FO-PID) control scheme, the authors of [252] also conclude that the performance of the FO-PID controller is higher than that of the NN-IMC [252].…”
Section: Artificial Neutral Network (Ann)mentioning
confidence: 99%
“…There are several other algorithms particle swarm optimization (PSO), genetic algorithm (GA), imperialistic competition algorithm (ICA), harmony search (HS), are available in the literature. The authors used BBBC [13] to identify the best parameters of an FOPID controller, after comparing it to other search algorithms such as ICA and GA [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%